Safety and efficacy of clinical-grade, cryopreserved menstrual blood mesenchymal stromal cells in experimental acute respiratory distress syndrome - Alcayaga-Miranda, Francisca; Dutra Silva, Johnatas; Parada, Nicol; Andrade da Silva, Luisa Helena; Ferreira Cruz, Fernanda; Utreras, Yildy; Hidalgo, Yessia; Cádiz, María Ignacia; Tapia Limonchi, Rafael; Espinoza, Francisco; Bruhn, Alejandro; Khoury, Maroun; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Treatment for critical care conditions, such as acute respiratory distress syndrome (ARDS), requires ready-to-administer injectable mesenchymal stromal cells (MSCs). A validated cryopreserved therapy based on MSCs derived from menstrual blood (MenSCs) is an attractive option that offers advantages over freshly cultured cells and allows its use as an off-the-shelf therapy in acute clinical conditions. The main goal of this study is to provide evidence on the impact of cryopreservation on different biological functions of MenSCs and to determine the optimal therapeutic dose, safety, and efficacy profile of clinical-grade, cryopreserved (cryo)-MenSCs in experimental ARDS. Methods: Biological functions of fresh versus cryo-MenSCs were compared in vitro. The effects of cryo-MenSCs therapy were evaluated in vivo in ARDS-induced (Escherichia coli lipopolysaccharide) C57BL/6 mice. After 24 h, the animals were treated with five doses ranging from 0.25×105 to 1.25×106 cells/animal. At 2 and 7 days after induction of ARDS, safety and efficacy were evaluated. Results: Clinical-grade cryo-MenSCs injections improved lung mechanics and reduced alveolar collapse, tissue cellularity, and remodelling, decreasing elastic and collagen fiber content in alveolar septa. In addition, administration of these cells modulated inflammatory mediators and promoted pro-angiogenic and anti-apoptotic effects in lung-injured animals. More beneficial effects were observed with an optimal dose of 4×106 cells/Kg than with higher or lower doses. Conclusion: From a translational perspective, the results showed that clinical-grade cryopreserved MenSCs retain their biological properties and exert a therapeutic effect in mild to moderate experimental ARDS. The optimal therapeutic dose was well-tolerated, safe, and effective, favouring improved lung function. These findings support the potential value of an off-the-shelf MenSCs-based product as a promising therapeutic strategy for treating ARDS.